Analisis Rasio Kecukupan Modal (CAR) Dan Loan To Deposit Ratio (LDR) Terhadap Return On Equity (ROE) Pada Perusahaan Perbankan Yang Terdaftar Di Indonesia Stock Exchange (IDX) - Milda Maulida; Idang Nurodin; Gatot Wahyu Nugroho (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to determine the effect of the variables Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) on Return On Equity (ROE). This study uses quantitative methods. The object of this research is the Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) and Return On Equity (ROE). This research method is in the form of numbers and analysis using statistics. The data analysis technique in this study used parametric statistics. The results of this study indicate that simultaneously and partially the variables Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) have a positive and significant effect on Return On Equity (ROE). Fcount 1.955 > Ftable 3.130 then H3 is accepted and H3 is rejected. So it can be concluded, Capital Adequacy Ratio and Loan to Deposit Ratio have no effect on Return On Equity. So it can be concluded, Capital Adequacy Ratio and Loan to Deposit Ratio have no effect on Return On Equity in Banking Companies listed on the Indonesia Stock Exchange (IDX). Meanwhile, from the results of the t-test value, namely Tcount 4.261 > 1.667, it shows that Tcount is greater than Ttable so it can be concluded that the Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) variables have an influence on Return On Equity (ROE). Keywords: Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Return On Equity (ROE)